Faecal immunochemical test to triage patients with abdominal symptoms for suspected colorectal cancer in primary care: review of international use and guidelines - van Melle, Marije (Fam Pract, 2020)
BACKGROUND: Recently, faecal immunochemical tests (FITs) have been introduced for investigation of primary care patients with low-risk symptoms of colorectal cancer (CRC), but recommendations vary across the world. This systematic review of clinical practice guidelines aimed to determine how FITs are used in symptomatic primary care patients and the underpinning evidence for these guidelines. METHODS: MEDLINE, Embase and TRIP databases were systematically searched, from 1 November 2008 to 1 November 2018 for guidelines on the assessment of patients with symptoms suggestive of CRC. Known guideline databases, websites and references of related literature were searched. The following questions were addressed: (i) which countries use FIT for symptomatic primary care patients; (ii) in which populations is FIT used; (iii) what is the cut-off level used for haemoglobin in the faeces (FIT) and (iv) on what evidence are FIT recommendations based. RESULTS: The search yielded 2433 publications; 25 covered initial diagnostic assessment of patients with symptoms of CRC in 15 countries (Asia, n = 1; Europe, n = 13; Oceania, n = 4; North America, n = 5; and South America, n = 2). In three countries (Australia, Spain and the UK), FIT was recommended for patients with abdominal symptoms, unexplained weight loss, change in bowel habit or anaemia despite a low level of evidence in the symptomatic primary care patient population. CONCLUSIONS: Few countries recommend FITs in symptomatic patients in primary care either because of limited evidence or because symptomatic patients are directly referred to secondary care without triage. These results demonstrate a clear need for research on FIT in the symptomatic primary care population.